Investigating the Slope Stability and Factor of Safety Properties of Soil Reinforced with Natural Jute Fibers under Different Rainfall Conditions - Kumar, Saurabh; Roy, Lal Bahadur (Engineering, Technology & Applied Science Research, 2023)
Heavy rainfall is often responsible for embankment failures. During intense rainfall, the embankment slope inclination is vital for slope stability. Some failures occur in the slope due to heavy rainfall and sudden change in the matric suction. Jute fiber is a reinforcing material that is added to improve soil strength. In this research, in order to explore the effects of slope inclination on soil stability, soil samples were collected and exposed to artificial rainfalls. This study presented various tests performed on the soil samples. Different tests like sieve analysis, permeability test, Direct Shear Test (DST), liquid limit, plasticity limit, and numerical modeling were conducted in the laboratory. The study’s findings revealed that the failure is caused by a soil suction loss when the inclination of the slope is higher than the soil friction angle and the collapse is caused by the positive water pressure at the slope’s toe when it is lower than the soil’s friction angle. Furthermore, when the slope angle increases, the slopes are becoming increasingly vulnerable to rapid collapse. After that, jute fibers were combined with the soil to improve its performance. Samples of 2, 3, and 4 rows of jute fibers were tested. These jute fiber samples performed better than the ones without fibers under different rainfall conditions. The distribution of jute fibers had a favorable influence on both strength measurements and safety aspects. Utilizing the factor of safety and matric suction, the performance of jute fiber samples is superior to those without jute fibers. Consequently, by adding jute fibers the stabilization of the soil is significantly improved along with its factor of safety.